Dictionary of archaeological terms : English-German / German-English = Archäologisches fachwörterbuch : Englisch-Deutsch / Deutsch-Englisch - Junghans, Marie-Christine, (Archaeopress, 2012)
This concise dictionary is intended to be helpful in the reading of archaeological books and publications, and in the writing of papers and articles in both English and German. The aim of this work is to help, in particular, students and on-site archaeologists to find quickly a word relating to a specific period, a specific area or a research field, in a book easy to carry everywhere; but this dictionary is also intended for those with a general interest in archaeology wishing to broaden their vocabulary.